IMPLEMENTASI HUKUM DAN PERLINDUNGAN SOSIAL BAGI KORBAN KEKERASAN DALAM RUMAH TANGGA - Najamuddin Najamuddin; Hasnawi Haris; Sopian Tamrin; Nurdia Nurdia (Universitas Negeri Makassar, 2023)
This study aims to determine (1) the forms of domestic violence; (2) forms of social protection for victims of domestic violence; (3) Implementation of legal protection against domestic violence. The research was conducted in the city of Makassar using a descriptive qualitative approach. Based on the source, the types of data used are primary and secondary data. Primary data obtained through the interview method. While secondary data is data obtained from various documents or published sources or other related sources. Informants were selected by purposive sampling as many as 17 people. The data is processed by condensing the data, modeling the data and drawing conclusions. The results of the study show that: (1) The forms of domestic violence are; physical violence, which is characterized by pain, serious injury and illness to the victim, psychological violence, as evidenced by loss of self-confidence, helplessness and psychological suffering, sexual violence is the force of balanced sexual relations and neglect of the household in the form of not giving decent living, not letting the public sector work outside the home; (2) The form of social protection against domestic violence is to report it to the authorities, by neighbors or relatives to intervene/obstruct the perpetrator and the victim, hide the victim from the scene; (3) Implementation of legal protection against domestic violence is that victims receive protection from their families, receive health services according to their medical needs, receive assistance from civil groups and spiritual guidance.